Metabolic dysfunction-associated steatotic liver disease increases hepatocellular carcinoma risk in chronic hepatitis B patients: a retrospective cohort study - Lin, Ming; Gao, Bowen; Peng, Mengnan; Chen, Xuefang; Xiao, Huanming; Shi, Meijie; Zhang, Xiujuan; Zeng, Folai; Chi, Xiaoling (Frontiers in Physiology, 2024)
The combined effect of hepatitis B virus infection and metabolic dysfunctionassociated steatotic liver disease (MASLD) on hepatocellular carcinoma (HCC) risk remains unclear. The current study sought to elucidate the impact of MASLD on HCC progression in chronic hepatitis B (CHB) patients.This retrospective cohort study included CHB patients who had undergone liver biopsy and abdominal imaging at the Guangdong Provincial Hospital of Chinese Medicine between 2013 and 2019. We investigated the correlation between MASLD and HCC risk, and inverse probability treatment weighting (IPTW) was used to adjust for patient characteristics.Results: A total of 1,613 patients were included, and 483 (29.9%) were diagnosed with MASLD. Over a median follow-up period of 5.02 years, 36 (2.2%) developed HCC, comprising 4.8% (23/483) of those with MASLD and 1.2% (13/1,130) of those without. Those with MASLD had a significantly higher cumulative incidence of HCC than those without (P < 0.001). The presence of MASLD was associated with a higher risk of HCC (adjusted hazard ratio [HR], 3.996; 95% confidence interval [CI], 2.007-7.959; P < 0.001). After adjustment using IPTW, the patients with MASLD retained a higher cumulative incidence of HCC (P < 0.001). Moreover, MASLD was found to be an independent risk factor for the development of HCC (adjusted HR, 10.191; 95% CI,; P < 0.001). However, among patients with MASLD, there were no significant differences in the cumulative risk of HCC between patients with and without overweight, between those with <2 and ≥2 cardiometabolic risk factors (CMRFs), between those with <3 and ≥3 CMRFs, or between those with <4 and ≥4 CMRFs (P = 0.110, P = 0.087, P = 0.066, and P = 0.490, respectively). 批注 [ML1]: The abstract has been rewritten based on the revised content. 批注 [ML2]: Incidence of HCC in the MASLD group and non-MASLD groups.The presence of MASLD is associated with a higher risk of HCC in patients with CHB. Notably, this higher risk is present in patients with MASLD, irrespective of the presence or absence of overweight or the number of CMRFs they have.